2016
DOI: 10.1515/mammalia-2014-0157
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and richness of small mammals at a well-conserved site of The Yungas in Jujuy Province, Argentina

Abstract: We present the results obtained from 12 small-mammal surveys conducted between 1996 and 2013 in “Finca Las Capillas”, province of Jujuy, Argentina. This region has been formally recognized as an “Area of Importance for the Conservation of Bats” (AICOM) based on the diversity of species detected in our previous studies. This site in the Yungas forests of northwestern Argentina still maintains an excellent conservation status due to restrictions to human activities involving deforestation and limitations to catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In other studies in Argentina, this species was also found roosting inside buildings (López Berrizbeitia & Díaz 2013;Lutz 2013). The high abundance of Sturnira lilium is also coincident with other several studies made in tropical (Kalko & Handley 2001) and subtropical environments (Moya et al 2008;Gamboa Alurralde et al 2016), where bat assemblages are dominated by frugivorous species. Although most species of bats are insectivorous (Shiel et al 1997), in tropical environments they are usually not the dominant guild, whereas at higher latitudes the importance of insectivores in the structure of bat communities increases, as recorded in this study.…”
Section: Discussionsupporting
confidence: 86%
“…In other studies in Argentina, this species was also found roosting inside buildings (López Berrizbeitia & Díaz 2013;Lutz 2013). The high abundance of Sturnira lilium is also coincident with other several studies made in tropical (Kalko & Handley 2001) and subtropical environments (Moya et al 2008;Gamboa Alurralde et al 2016), where bat assemblages are dominated by frugivorous species. Although most species of bats are insectivorous (Shiel et al 1997), in tropical environments they are usually not the dominant guild, whereas at higher latitudes the importance of insectivores in the structure of bat communities increases, as recorded in this study.…”
Section: Discussionsupporting
confidence: 86%
“…The Yungas Forests have the greatest number of species of fleas, followed by the Monte Desert of Mountains and Isolated Valleys, Dry Chaco, High Andes, and Puna. The higher diversity in the Yungas Forests is a reflection of an area with the greatest diversity in the Neotropical region (Mittermeier et al 1999), including mammals (Barquez et al 2006;Gamboa-Alurralde et al 2015) with the sigomodontine rodents and bats (Díaz and Barquez 2007;Barquez and Díaz 2009;Gamboa Alurralde et al 2016; Gamboa Alurralde 2017). These small mammals were the main hosts for the families Rhopalopsyllidae and Ischnopsyllidae, two of the most diverse in the Yungas Forests.…”
Section: Discussionmentioning
confidence: 99%
“…2). The new record of H. velatus from the province of Salta adds a new locality to Northwestern Argentina, because the only known previous record was from Jujuy province (Barquez andDíaz 2001, 2007;Barquez 2006;Gamboa Alurralde et al 2016). The first records of this species for Argentina were obtained in 1970 in the province of Misiones, while the specimens from Jujuy (in the northwest) were obtained in 1997, almost 30 years later, and then recently in 2012, after continuous efforts for collecting bats, which reflects the scarcity and rarity of the species in the country.…”
Section: Discussionmentioning
confidence: 94%